The Risk Factors of Puberty Precocious in Girls: Is the Condition Related with Polychlorobiphenyls? - Raziye Burcu Güven Bilgin; Samim Özen; Ruhsar Damla Gökşen; Özlem Korkmaz; Şükran Darcan (Galenos Yayinevi, 2021)
Aim:Our aim was investigate the effect of polychlorobifenyls (PCBs) and other factors on puberty precocious (PP) in girls were diagnosed with idiopatic PP and premature thelarche (PT).Materials and Methods:The study group included 50 girls aged between 2-8 years old with PP and PT. The control group included 50 healthy girls with same age range and no puberty findings. Data was collected in terms of breast and pubic hair stages, weight, height, body mass index (BMI), standard deviation scores (SDSs), location of residence, gestational age and maternal age at menarche (AAM). Twenty-one PCB levels were evaluated in serum and urine. One-Way ANOVA test was used for comparison between the groups. For subgroup analysis, Mann-Whitney U test, multiple regression analysis were used.Results:The mean age of the study and control groups were 6.70±1.20 and 5.23±1.25 years, respectively. The studied PCBs were not detectable found in either the study or the control groups. The BMI SDSs of the patients in study and healthy groups were 0.49±1.09 and -0.12±1.28, respectively (p=0.1). Weight SDSs in the study group were found to be significantly higher than healthy group (0.72±1.35 vs -0.20±1.47, p=0.008 Maternal AAM of the patients in study group was significantly lower (p=0.006). In study group 98% of the patients were living in down town and district, whereas this ratio was 92% in control group (p=0.024). In study group 29 patients (58%) were diagnosed with PT. Basal follicle stimulating hormone and estradiol levels, bone age and uterine longest axis dimensions results were significantly different.Conclusion:We found that studied PCBs don't influence on PP in girls aged between 2-8 years old. However, weight SDS, maternal AAM, location of residence of the patients had a significant role on PP in this patient population.